Políticas alimentares e as capacidades estatais em capitais metropolitanas brasileiras - Silvia Aparecida Zimmermann; Catia Grisa; Adriana Aranha (Confins)
Food and agriculture have become topics of great interest in the 21st century. The urbanization of societies, threats to production caused by global warming and the intensification of inequality and nutritional food insecurity are some of today's challenges. This article analyzes and compares the State capabilities of two Brazilian metropolises in conducting food policies, Curitiba and Belo Horizonte. Both were pioneers in the creation of food policies in the mid-1980s, which persist to this day. The methodology used a bibliographic and documentary review and 23 semi-structured interviews with (former) secretaries, (former) managers and civil society representatives working in the two municipalities, between the months of March and August 2021. It is concluded that several factors contributed to the construction and continuity of food policies in the cities studied, especially institutional activism and bureaucratic structuring, in addition to training in food and nutritional security and the incorporation of the principles of efficiency and public innovation, as well as the recognition of food policies by the population local and national and international recognition of food themes.